PET/CT Imaging Basics and Practice - Agrawal, Kanhaiyalal; Skillen, Annah; Esmail, Abdulredha; Usmani, Sharjeel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The aim of this book is to provide concise information and quick reference on the basics and practice of PET/CT for beginners. The chapters are written by Nuclear Medicine experts from different countries with enormous experience in PET/CT practice. Starting with the basics of PET/CT describing physics and the use of radiopharmaceuticals in PET/CT, the book explores the principle of PET/CT in radiotherapy planning. The last five chapters explore normal variation, pitfalls and artefacts commonly seen with various routinely used PET radiotracers. The text is enriched by tables and highlighted clinical cases for better understanding. This book will be of interest mostly to nuclear medicine physicians and radiologists, but it may be appealing also to a wider medical community including oncologists and radiotherapists.
Chapter 1. Basic Principles of PET-CT imaging -- Chapter 2: Physics of PET and Respiratory Gating -- Chapter 3. The Physics of PET/CT for Radiotherapy Planning -- Chapter 4. 18F-FDG and Non-FDG PET Radiopharmaceuticals -- Chapter 5. PET/CT imaging: Patient instructions and preparation -- Chapter 6.18F-FDG PET/CT Imaging: Normal variants, pitfalls and artefacts.-Chapter 7: 68Ga-DOTA-peptides PET-CT: Physiological biodistribution, variants and pitfalls -- Chapter 8. 18F-methylcholine (FCH) PET-CT imaging: Physiological distribution, pitfalls and imaging pearls -- Chapter 9: 68Ga-PSMA PET/CT: Normal Variants, Pitfalls and Artefacts -- Chapter 10: 18F-NaF PET-CT Imaging.
Keywords: Nuclear medicine; Radiology; Medical radiology; Oncology; Nuclear Medicine; Radiology; Radiation Oncology; Positron-Emission Tomography; Tomography, X-Ray Computed